2018
DOI: 10.1097/rnj.0000000000000142
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic Exercise Program for Individuals With Osteoarthritis: Pain, Stiffness, Physical Function, Self-Efficacy

Abstract: The aquatic exercise program can be used by nurses as a reference in the management of osteoarthritic patients' health status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 23 publications
0
13
0
4
Order By: Relevance
“…Eleven studies were included in the meta-analysis with outcome assessed pain. WOMAC pain [ 24 , 28 , 31 , 33 , 34 ], VAS score [ 12 , 29 31 , 34 ], and KOOS pain [ 12 , 23 , 26 , 27 ] were used to measure pain. Studies which used WOMAC pain and VAS showed high heterogeneity (WOMAC pain: p < 0.1, I 2 = 93%, VAS: p < 0.1, I 2 = 73%), whereas KOOS pain showed low heterogeneity ( p = 0.85, I 2 = 0%).…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies were included in the meta-analysis with outcome assessed pain. WOMAC pain [ 24 , 28 , 31 , 33 , 34 ], VAS score [ 12 , 29 31 , 34 ], and KOOS pain [ 12 , 23 , 26 , 27 ] were used to measure pain. Studies which used WOMAC pain and VAS showed high heterogeneity (WOMAC pain: p < 0.1, I 2 = 93%, VAS: p < 0.1, I 2 = 73%), whereas KOOS pain showed low heterogeneity ( p = 0.85, I 2 = 0%).…”
Section: Resultsmentioning
confidence: 99%
“…3 Specifically, the properties of water provide unique opportunities for rehabilitation through the hydrostatic and hydrodynamic principles of buoyancy and resistance, 28 which consequently contributes to the reduction of pain, stiffness and difficulty in physical functions, as well as to the increase in the self-efficacy of motor movements in people with reduced mobility. 29 Consequently, physically active older adults throughout life have higher levels in terms of physical and cognitive function, mobility, less musculoskeletal pain, lower risk of falls and fractures, depression, better quality of life, 1 so the results of this systematization suggest the inclusion of aquatic exercises in programs for older adults to improve their functional capacity. Although, this study has some limitations, since the search for information was performed in only one database and covered 5 years (2017 to 2021), so future studies should expand the search for information not only in other databases, but also the range of years.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this exploratory study was to evaluate the immediate effects of one aquatic therapy session in a patient’s group older than 55 years, following a wash-out period of no aquatic therapy after the summer vacation. Many studies look for improvements due to longer interventions [ 6 , 8 , 25 , 30 , 33 , 36 , 37 ], but in this study, the key point was to find what changes occur immediately after a single training session. The literature showed significant benefits in several patient groups [ 47 ], however, the outcome measures used in previous studies were not consistent.…”
Section: Discussionmentioning
confidence: 99%
“…The literature showed significant benefits in several patient groups [ 47 ], however, the outcome measures used in previous studies were not consistent. Due to the limited time for assessment, researchers chose measures relevant to the health problems of the participants, as well as valid, reliable, and sensitive to training [ 6 , 17 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation